Penyuluhan Pembuatan Pupuk Kompos Dalam Rangka Gerakan Lumbung Hidup Rating Aisyiyah Kroman - Norainny Yunitasari; Janatun Na'imah; Diah Ratnasari (LPPM UNS, 2025)
The Aisyiyah Living Granary Movement (GLHA) is carried out to utilize empty land to meet food needs. One important thing in this movement is the community's understanding of how to obtain fertile planting media and support plant growth, namely by making compost. The purpose of this activity is to strengthen the community's understanding (especially members of the Aisyiyah Kroman Branch) in efforts to make compost independently. The activity method used is counseling (lectures). The results of the activity show that this activity can encourage the enthusiasm of participants to ask questions and explore the manufacture of organic fertilizer (compost). In making this compost, two types of results can be obtained, namely liquid and solid fertilizer. This is different from eco enzyme fertilizer which is only liquid. The two types of fertilizers also differ in terms of the smell produced, organic fertilizer (compost) has an unpleasant odor, while eco enzyme fertilizer has a fresher odor.